Recent high school graduates support mandatory cardiopulmonary resuscitation education in Australian high schools. (4th May 2020) - Rankin, Tim; Holmes, Lisa; Vance, Leanne; Crehan, Tom; Mills, Brennen
Abstract: Objective : To evaluate recent high school graduates' opinions on mandatory cardiopulmonary resuscitation (CPR) training in the high school curriculum as a solution to improving bystander CPR rates. Methods : Participants completed questionnaires assessing their CPR training history during their high school education, their willingness to learn CPR during their high school years and their opinion on making CPR training mandatory for high school curricula. Results : Of the 178 participants in this study, 60% had undertaken CPR training during their high school education. Of those who had not undertaken CPR training, 75% reported that they would have been willing to learn CPR had they been provided with the opportunity. A total of 97% of participants were in support of mandatory CPR training in high school education. Conclusion : Implementing mandatory CPR training in high school education would be embraced by students. Implications for public health : Findings of this study support our recommendation to implement mandatory CPR training in the high school curriculum. This will likely increase the number of bystanders in the community who would spontaneously administer CPR, thereby improving outcomes for patients experiencing out‐of‐hospital cardiac arrest.